A Signal‐Passing DNA‐Strand‐Exchange Mechanism for Active Self‐Assembly of DNA Nanostructures1. Issue 20 (24th March 2015) - Padilla, Jennifer E.; Sha, Ruojie; Kristiansen, Martin; Chen, Junghuei; Jonoska, Natasha; Seeman, Nadrian C.
Abstract DNA nanostructured tiles play an active role in their own self‐assembly in the system described herein whereby they initiate a binding event that produces a cascading assembly process. We present DNA tiles that have a simple but powerful property: they respond to a binding event at one end of the tile by passing a signal across the tile to activate a binding site at the other end. This action allows sequential, virtually irreversible self‐assembly of tiles and enables local communication during the self‐assembly process. This localized signal‐passing mechanism provides a new element of control for autonomous self‐assembly of DNA nanostructures.